How do libraries manage the ethical and privacy issues of RFID implementation? A qualitative investigation into the decision-making processes of ten libraries. (June 2015) - Ferguson, Stuart; Thornley, Clare; Gibb, Forbes
This paper explores how library managers go about implementing RFID (radio frequency identification) technology and particularly how associated privacy issues have been managed. The research methodology consisted of a literature review, theme identification, interview scheduling, interviews and interview analysis. The sample was 10 libraries or library networks and 18 participants. Findings covered the main drivers of RFID development, perceived benefits, tag data, data security, levels of ethical concern, public consultation, potential impact of technological developments on ethical issues, and managers' sources of ethical decision making. Analysis of potential ethical issues was not found to be a central part of the process of implementing RFID technology in the libraries. The study sees RFID implementation as an informative example of current practice in the implementation of new technologies in libraries and suggests that we look at management structures and decision-making processes to clarify where responsibility for ethical considerations should lie.